1996
DOI: 10.1017/s0142716400009462
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prosodic modeling and repeated reading on poor readers' fluency and comprehension

Abstract: Repeated reading of meaningful text has been shown to produce improvements in reading rate, fluency, and comprehension in readers of varying ability. The assisted repeated reading (ARR) method, which provides a fluent and expressive (i.e., prosodic) model, has been proposed as being particularly helpful in this regard. However, it is unclear which component of the ARR method (prosodic modeling or reading practice with intact text) is the most influential factor. The present study examined the effects of text p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 25 publications
5
39
0
5
Order By: Relevance
“…Although part of the comprehension gains may stem from the experience of having responded to the recall questions at pretest, gains for trained passages were greater than for untrained passages, indicating that RR training supports comprehension of trained passages. Our results fall in line with others who found comprehension gains after RR training with text (Dowhower, 1987;O'Shea, Sindelar, & O'Shea, 1985;Young, Bowers, & MacKinnon, 1996) and word lists (Levy et al, 1997;Tan & Nicholson, 1997).…”
Section: Effects Of the Training On Comprehensionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although part of the comprehension gains may stem from the experience of having responded to the recall questions at pretest, gains for trained passages were greater than for untrained passages, indicating that RR training supports comprehension of trained passages. Our results fall in line with others who found comprehension gains after RR training with text (Dowhower, 1987;O'Shea, Sindelar, & O'Shea, 1985;Young, Bowers, & MacKinnon, 1996) and word lists (Levy et al, 1997;Tan & Nicholson, 1997).…”
Section: Effects Of the Training On Comprehensionsupporting
confidence: 93%
“…Students continued with assisted RR until they could read the book easily without support. In a later study, Conte and Humphreys (1989) confirmed that RR training with audio-taped text enhanced reading accuracy in older poor readers (see also Morgan & Lyon, 1979;Young, Bowers, & MacKinnon, 1996).…”
mentioning
confidence: 73%
“…Reading texts proficiently suggests to us that necessary foundational fluency competencies must be in place that enables readers to focus their cognitive resources on creating meaning from the text (McCormick & Samuels, 1979;Perfetti & Hogaboam, 1975;Samuels & Farstrup, 2006). This suggests that there is a reciprocal relationship between fluency and comprehension while fluency has been repeatedly shown to be a necessary condition for effective comprehension (Paige, 2011a;Fuchs, Fuchs, Hosp, & Jenkins, 2001;Jenkins, Fuchs, Espin, van den Broek, & Deno, 2003a, 2003bKuhn & Stall, 2003;Pinnell, Pikulski, Wixon, Campbell, Gough, & Beatty, 1995;Schatschneider, Buck, Torgesen, Wagner, Hassler, Hecht et al, 2004;Stecker, Roser, & Martinez, 1998;Young, Bowers, & MacKinnon, 1996). A major shift within CCSS is the increased importance of comprehending informational texts across grade levels.…”
Section: Introductionmentioning
confidence: 99%
“…However, the practical value of this type of treatment can be higher if transfer of training effects are found. The few experiments that have studied transfer have failed to find substantial generalisation of repeated reading training effects to untrained material (Lemoine, Levy, & Hutchinson, 1993;Young, Bowers, & MacKinnon, 1996; for an overview of repeated reading training studies, see Wolf & Katzir-Cohen, 2001). It appears that repeated reading leads to high levels of fluency for trained words, but has little benefits for general reading skill.…”
Section: Introductionmentioning
confidence: 99%